Hsa_circ_0001955 Promotes Colorectal Cancer Progression by Regulating miR-583/FGF21 Axis. (11th May 2022) - Gao, Xuefeng; Yin, Junfeng; Yao, Ying
Abstract : Objective . Hsa_circ_0001955 presents significant upregulation in colorectal cancer (CRC) tissues. However, its role in CRC remains unclear. Thus, we attempted to clarify functions of hsa_circ_0001955 on CRC. Methods . qRT-PCR was performed to examine hsa_circ_0001955, miR-583, and FGF21 levels. Western blotting was conducted to measure FGF21 protein expression. CCK-8, flow cytometry, and Ki-67 immunohistochemical staining and TUNEL assays were conducted to assess proliferation and apoptosis in vitro and in vivo, respectively. Cell invasion and migration were assessed by Transwell assay. Tumor-bearing mouse model and HE staining were used to assess inflammatory injury. Luciferase reporter system and RNA pull-down were conducted to evaluate the regulation between miR-583 and hsa_circ_0001955 or FGF21. Results . We found that hsa_circ_0001955 showed characteristics of upregulated circRNA in CRC. Further analysis indicated that hsa_circ_0001955 elevation facilitated CRC cell malignancy in vitro and promoted tumor growth in vivo . Furthermore, hsa_circ_0001955 was a miR-583 sponge and FGF21 was directly targeted by miR-583. In addition, we found that downregulation of miR-583 promoted hsa_circ_0001955-mediated CRC cell malignancy in vitro . In contrast, FGF21 elevation promoted miR-583-regulated CRC cell malignancy in vitro . Conclusion . We demonstrated that hsa_circ_0001955 facilitated CRC progression via miR-583/FGF21 axis, suggesting that hsa_circ_0001955 may provide a novel insight for therapy of CRC.